Association between dietary multi-metal intake and the risk of diabetic retinopathy: a population-based study - Zhang, Chaohua; Peng, Haiyang; Lang, Qin; Fang, Haoyu; Zhang, Keqin; Zhao, Andong (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the association between dietary metals intake and the risk of diabetic retinopathy (DR) in adults with diabetes.MethodsData from 2,822 U. S. adults with diabetes in National Health and Nutrition Examination Survey (NHANES) 2007–2016 were analyzed. Associations between the intake of six dietary metals and DR risk were assessed using multivariable logistic regression, Weighted Quantile Sum (WQS) regression, and Bayesian Kernel Machine Regression (BKMR). Restricted Cubic Spline (RCS) regression examined the dose–response relationship between intake of dietary metal and DR risk. Mediation analysis explored the underlying mechanisms.ResultsLog10-transformed dietary Zinc (Zn) (OR = 0.53, 95% CI 0.35–0.80, p = 0.003) were negatively associated with the DR risk. WQS regression indicated that the combined effects of dietary metals intake were negatively associated with the risk of DR (OR = 0.79, 95% CI 0.61–0.97, p = 0.024), with Zn contributing the most to the reduced risk (36.4%). BKMR model suggested the negative association between the combined intake of 6 metals and DR risk, with Zn receiving the highest posterior inclusion probability (PIP) (0.8574).ConclusionIn American adults with diabetes, elevated dietary metals intake, especially zinc, may be associated with a lower risk of DR.